2023
DOI: 10.32604/cmes.2022.021494
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid BPNN-GARF-SVR Prediction Model Based on EEMD for Ship Motion

Abstract: Accurate prediction of ship motion is very important for ensuring marine safety, weapon control, and aircraft carrier landing, etc. Ship motion is a complex time-varying nonlinear process which is affected by many factors. Time series analysis method and many machine learning methods such as neural networks, support vector machines regression (SVR) have been widely used in ship motion predictions. However, these single models have certain limitations, so this paper adopts a multi-model prediction method. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Addressing the intricacies associated with predicting the purchase value of military aircraft, a devised SVR prediction model analyzed the impact of individual parameters, yielding heightened prediction accuracy [ 16 ]. Other than that, studies done by previous researchers showed that local optimal solutions can be obtained by SVR to increase its accuracy [ 17 , 18 ], and the method to solve the problem of nonlinear fitting has also been shown [ 19 , 20 ]. Moreover, other applications such as solving electric load forecasting [ 21 ] or constructing predictive models using the scikit-learn module have been shown using SVR [ 22 , 23 ].…”
Section: Svr Applicationsmentioning
confidence: 99%
“…Addressing the intricacies associated with predicting the purchase value of military aircraft, a devised SVR prediction model analyzed the impact of individual parameters, yielding heightened prediction accuracy [ 16 ]. Other than that, studies done by previous researchers showed that local optimal solutions can be obtained by SVR to increase its accuracy [ 17 , 18 ], and the method to solve the problem of nonlinear fitting has also been shown [ 19 , 20 ]. Moreover, other applications such as solving electric load forecasting [ 21 ] or constructing predictive models using the scikit-learn module have been shown using SVR [ 22 , 23 ].…”
Section: Svr Applicationsmentioning
confidence: 99%
“…In recent years, the modeling methods based on machine learning theory [8][9][10][11] have attracted considerable attention from researchers. In the process of modeling by machine learning, there is no need to consider the degree of nonlinearity between input and output.…”
Section: Introductionmentioning
confidence: 99%